Inovação nas condições de cultivo visando o melhoramento da produção de vacina contra erisipela suína - Machado, Maria Manuela Pereira (2010)
Pork is one of the most widely eaten meats in the world and pig farming is an economic activity booming in Brazil and the world. Several efforts have been made to develop more effective vaccines for major diseases that are affecting livestock such as swine erysipelas, caused by the bacterium Erysipelothrix rhusiopathiae. The currently available vaccines for the prevention of erysipelas are produced with culture broth of this microorganism inactivated or attenuated. The main antigenic agent identified is an protein fraction of 64-69 kDa, present in cell wall of bacteria and the supernatant of the culture. Given the accumulated knowledge of the studies conducted by Silva (2007), this study aimed to: i) study the conditions employed in the preparation of cell suspension for freezing and formation of culture stocks in crytubes and the stage of their activation; ii) studying the growth of E. rhusiopathiae, the formation of lactic acid and expression of antigen in culture media containing carbon sources alternative to glucose and in culture media containing nitrogen sources of plant origin; iii) to study the behavior of the microorganism in the new culture medium, animal-free, in a bioreactor. The studies for the improvement of the medium formulation were carried out in flasks incubated at static condition or under agitation of 200 rpm. The temperature was set at 37°C and the initial pH at 8,0 in all experiments. The studies in bioreactor were made using a 4.0 L stirred-tank bioreactor, with an agitation frequency kept between 100 and 700 rpm and air flow rate of 1.0 L/min. Samples of cell extracts made with choline chloride were analyzed by electrophoresis under denaturating conditions (SDS-PAGE) to evaluate the antigen expression. Studies of activation of the criotubes containing frozen cell suspensions led to the standardization of this step, with high reproducibility, and reduced activation time by 50%. The studies were grew with different carbon sources, showing that E. rhusiopathiae is able to assimilate galactose, lactose, and glucose. However, there was no assimilation of glycerol. The replacement of proteose peptone, a nitrogen source animal widely used in the cultivation of E. rhusiopathiae to produce bacterins, by Soytone, a soy peptone, animal-free, was a promising alternative for the production of the inactivated vaccine, helping to increase the specific growth rate and substrate conversion of cells in relation to values obtained in conventional medium. In batch cultivation performed in a bioreactor with medium containing glucose and Soytone, it was reached a biomass concentration of 10 g / L at 5 hours of cultivation. For the conventional medium, containing proteose peptone, the maximum cell concentration reported for the test batch in a bioreactor was approximately 2 g / L, which was reached after 7 hours of culture. Note also that a higher level of expression of antigenic protein in relation to those observed with peptone of animal origin was achieved in cultures performed with medium containing soytone.This result shows that could be incorporate the best practices of manufacturing practices for pharmaceutical and veterinary products, subject to the productivity of the process and with significant cost reduction.